O-9 Reflections on an evolving @weeolc twitter community influencing clinical practice, leadership, quality and self. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Russell, Sarah; Johnston, Bridget; Green, Laura
Abstract : Background: Three clinical academic nurses with palliative care backgrounds established @WeEOLC as part of the @WeNurses Twitter community in October 2015. The social media platform Twitter has the potential to influence care through the sharing of knowledge and practice as well as provoking discussion and debate (Russell et al ., 2015). The focus of this abstract is to consider whether Twitter can assist in the achievement of improving evidence-based practice in palliative and end-of-life care through the learning outcomes framework of clinical practice, leadership, quality improvement and developing self (Taylor 2016). Aim: To share reflections on the value of engagements of @WeEOLC. Method: Established the twitter handle @WeEOLC #WeEOLC to start and join in conversations. Scheduled regular chats with diverse guest hosts. Provided regular signposting of links to articles, blogs and resources. Analysis of chats and conversations. Results: Analysis of chats, contributor profiles and timelines provide rich insights into online activity. Simply counting the number of contributors and tweets does not reveal the full influence of @WeEOLC. Chat and conversation contributors come from a wide background (e.g. clinicians, non-clinical, academics in social sciences, patients, families and interested parties). There is evidence of new connections and partnerships as well as a broad scope of interactive discussions, shared resources, evidence and reflections. Conclusion: Participation in platforms such as Twitter can support clinical and academic roles. By providing a non-hierarchical forum for learning and sharing, it contributes to clinical care, leadership and quality. Future work needs to develop methods of analysing and disseminating qualitative content as well as the quantitative reach of Twitter engagement.